IMPLEMENTASI ELECTRONIC PUBLIC RELATIONS (E-PR) DI SEKOLAH DASAR: STRATEGI KOMUNIKASI DIGITAL BERBASIS PRINSIP DIALOGIS - Paryanti Paryanti; Rustam Ibrahim (STKIP Pesisir Selatan, 2026)
The rapid growth of digital technology has transformed public relations practices in elementary education institutions. Elementary schools no longer rely solely on conventional communication methods but increasingly utilize digital media such as WhatsApp, Instagram, Facebook, and websites to establish relationships with parents and communities. This study aims to: (1) analyze digital communication strategy patterns implemented in elementary schools through Electronic Public Relations (E-PR); (2) identify the gap between dialogic communication concepts and field practices; and (3) formulate strategic recommendations for school public relations managers. This research employed a qualitative approach using a Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Data were collected from national and international scholarly articles published between 2021 and 2025 and accessible through Google Scholar, Scopus, DOAJ, and SINTA databases. The findings reveal that E-PR implementation in elementary schools is dominated by the use of WhatsApp and social media platforms for operational communication and school promotion activities. However, the implementation of dialogic communication principles such as mutuality, empathy, and openness to dialogue remains relatively weak. The primary obstacles include limited digital human resources, inadequate budgets, and low levels of digital literacy among some parents. This study proposes strengthening the dialogic communication model through the principles of accessibility and sustainability in the context of elementary schools in developing countries.